CARICOM standards for the teaching profession: Teachers, educational leaders and teacher educators - CARICOM Secretariat (CARICOM Secretariat, 2020)
The CARICOM Standards for the Teaching Profession is an aspirational collection of statements of performance and value expectations for members of the teaching profession in the CARICOM region. It is designed based on the following principles: 1. That being stirred into the profession of teaching is developmental and occurs within communities of practices. As such, no individual is fully developed as a teacher upon graduation from teacher training and the potential for growth should be aligned with career development. 2. That even before teachers graduate from their teacher education programme they are focused on the progression of their career. However, it is important to note that there is no clear and direct path to progression in the teaching service since teachers enter the teaching service at different competency levels. Therefore, the single trajectory of individuals will vary. In this regard, this document offers guidelines to assist with career progression in the teaching service. While it is important to acknowledge that years of focus to career progression. service provide significant experience toward teacher progression, factors such as competence to perform the tasks expressed in this document, knowledge and attitude as well as feedback from performance appraisals and colleagues must be of central 3. That good classroom teachers are not automatically good leaders; as such their leadership development must begin at the point of being a teacher candidate in training, through to the classroom and be sustained throughout their leadership career. 4. That the expectations for teacher educators must be aligned with those for effective and innovative classroom teachers and entrepreneurial school leaders. More so, teacher educators play a key role in developing and nurturing evidence-based practices in teaching. As such, teacher educators carry the burden of mentoring scholastic leadership. 5. That students, parents and the wider community should be fully aware of, and come to an agreement around, the sets of expectations a society should have for members of its teaching force; while ensuring the wellbeing of the teaching profession. Thus, the standards are deliberately written in an accessible manner that is aimed at holding the teacher accountable for the cultural and political obligations that s/he carries for the society. Thus, while the standards for classroom teachers, educational leaders and teacher educators, can be read in isolation, it is recommended that the document be considered in its entirety. The document should be used as a guide for education systems to develop professional standards where none exist and where they do exist it is a reference framework that can be used to strengthen existing policies and procedures that govern assessing teaching quality.
Approved at the 38th Meeting of the Council for Human and Social Development (COHSOD)- Education, 23- 24 October 2019
Keywords: CARICOM standards; teaching profession; educational leaders; teaching quality